Reaction of facultative cultivars of spring wheat to autumn and spring sowing dates - Jarecki, Wacław; Bobrecka-Jamro, Dorota (Polish Journal of Agronomy, 2019)
The aim of the study was to evaluate the reaction offacultative cultivars of spring wheat to autumn and spring sowingdates. Sowing of facultative cultivars in autumn is justifiedespecially after late forecrop (sugar beet, maize for grain), whenthe optimal date of sowing of winter wheat has passed. A replicatedfield experiment was carried out in the seasons 2013/2014?2015/2016. Three cultivars of spring wheat: Bombona, OstkaSmolicka and Struna were selected for testing. The autumn vs.spring sowing date of spring wheat was shown to result in a significantincrease in rain yield (by 0.7 t ha-1, i.e. 10.8%). The yieldincrease was the result of an increased number of ears per m2and 1000 grain weight in cultivars from autumn sowing. Grainfrom spring sowing was characterized by a higher content of totalprotein, phosphorus, calcium, iron, copper and zinc. The autumnsowing date resulted in an increase in the content of potassiumin the grain. Struna was marked by a significantly larger numberof ears per m2 compared to that in Ostka Smolicka. Bombonaformed a greater number of grains in the ear than Struna, but itdeveloped smaller grains compared to those in Ostka Smolicka.Bombona had the highest total protein and ash content. The grainof Struna contained significantly more starch than Bombona andless crude fibre than Ostka Smolicka. Bombona had a highercontent of phosphorus compared to that in Struna, and a highercalcium content than Struna and Ostka Smolicka. High contentsof iron, copper and manganese was determined in the grain ofBombona , whereas the grain of Ostka Smolicka was high in zinc.